Concrete for prefabricated lining segment and preparation method thereof

By using modified polycrystalline mullite fibers and porous fillers in concrete lining pipe sheets, the problems of easy damage and poor fire resistance in the prior art are solved, and high strength, crack resistance and fire resistance are achieved and anti-burst effects.

CN119430755APending Publication Date: 2025-02-14QINGDAO EVERBRIGHT GRP LARGE COMPONENTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411491819.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing concrete lining pipe sheets are prone to breakage and cracks, have poor fire resistance, and increase brittleness when improving crack resistance, affecting durability and safety.

Method used

Prefabricated concrete for lined pipe sheets using modified polycrystalline mullite fibers and porous fillers. Modified polycrystalline mullite fibers are made of polycrystalline mullite fibers loaded with alumina nanowire aerogel, combined with phenyl silicon The resin adheres to form a mesh structure, improving tensile strength and heat insulation effect.

Benefits of technology

It significantly improves the crack resistance, fire resistance and burst resistance of concrete, reduces the possibility of heat expansion and burst, and enhances the durability and safety of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100279550000081
    Figure BDA0005100279550000081
  • Figure BDA0005100279550000091
    Figure BDA0005100279550000091
  • Figure BDA0005100279550000111
    Figure BDA0005100279550000111
Patent Text Reader

Abstract

The invention relates to the field of building materials, and particularly discloses concrete for a prefabricated lining segment and a preparation method of the concrete. The invention discloses concrete for a prefabricated lining segment. The concrete is prepared from the following raw materials in parts by weight: 380 to 400 parts of cement, 720 to 750 parts of sand, 1135 to 1200 parts of stones, 130 to 150 parts of water, 50 to 60 parts of fly ash, 5.16 to 5.5 parts of an additive, 90 to 100 parts of modified polycrystalline mullite fibers and 45 to 50 parts of porous filler, the modified polycrystalline mullite fiber comprises polycrystalline mullite fiber and alumina nanowire aerogel loaded on the surface of the polycrystalline mullite fiber, and the mass ratio of the polycrystalline mullite fiber to the alumina nanowire aerogel is 1: (0.2-0.4). The concrete for the lining segment is high in compressive strength, good in crack resistance, excellent in high-temperature resistance, high in fire resistance and not prone to cracking at the high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and more specifically, to a concrete for prefabricated lining segments and a preparation method thereof. Background Art

[0002] With the increasing congestion of urban traffic, building subways has become the main way to ease urban traffic pressure. At present, most major cities in my country have subways, and my country's subway construction has entered a stage of rapid development. As an important part of the tunnel support system and tunnel structure, the precast concrete lining segment is the outermost barrier of the tunnel, responsible for resisting soil pressure, groundwater pressure and some special loads. Its quality is directly related to the overall quality and safety of the tunnel.

[0003] In engineering practice, the defects of concrete lining segments have gradually become apparent, mainly including: 1. They are easy to break and crack, which destroys the integrity of the concrete lining segments, causes leakage and corrosion, and has an adverse effect on the safety and durability of the tunnel structure; 2. Poor fire resistance. Traditional reinforced concrete segments have not taken fire factors into consideration. Once a fire occurs, the concrete segments are prone to bursting, exposing the internal steel bars, thereby causing local or even overall structural damage.

[0004] At present, in order to improve the crack resistance of concrete lining segments, the commonly used method is to increase the strength grade of concrete. However, this method only simply increases the strength of concrete and increases the brittleness of concrete, which in turn affects the crack resistance of concrete and makes it easy for concrete to burst when subjected to high temperatures.

[0005] In view of the above-mentioned related technologies, it is urgent to provide a concrete lining segment with high strength, crack resistance, fire resistance and explosion resistance. Summary of the invention

[0006] In order to improve the crack resistance and fire resistance of lining segments, the present application provides concrete for prefabricated lining segments and a preparation method thereof.

[0007] In a first aspect, the present application provides a prefabricated lining segment concrete, which adopts the following technical solution: A concrete for prefabricated lining segments, comprising the following raw materials in parts by weight: 380-400 parts of cement, 720-750 parts of sand, 1135-1200 parts of stone, 130-150 parts of water, 50-60 parts of fly ash, 5.16-5.5 parts of admixture, 90-100 parts of modified polycrystalline mullite fiber, and 45-50 parts of porous filler; The modified polycrystalline mullite fiber comprises polycrystalline mullite fiber and alumina nanowire aerogel loaded on the surface thereof, and the mass ratio of the polycrystalline mullite fiber to the alumina nanowire aerogel is 1:0.2-0.4.

[0008] By adopting the above technical solution, the porous filler can change the pore structure and distribution of concrete due to the voids inside it. These pores can reduce the internal stress concentration to a certain extent, which helps to improve the crack resistance of concrete. The modified polycrystalline mullite fiber can avoid the adverse effect of the use of porous fillers on the tensile strength of concrete to a certain extent. Moreover, the large number of pores in the porous filler can reduce the thermal conductivity of concrete, thereby improving the thermal insulation effect of concrete and reducing the possibility of concrete bursting due to heat.

[0009] The modified polycrystalline mullite fiber contains alumina nanowire aerogel, which is a three-dimensional structure aerogel constructed by one-dimensional nanomaterials, and has the advantages of low thermal conductivity, high specific surface area and high thermal stability. In addition, the alumina nanowire aerogel has strong nanoactivity and has a certain promoting effect on cement hydration, so it can improve the compressive strength of concrete. In addition, the thermal conductivity of polycrystalline mullite fiber is only 0.12W / (m·K) at room temperature, and the thermal conductivity is low. It has good thermal insulation effect and can slow down the bursting of concrete at high temperature. If part of the polycrystalline mullite fiber decomposes under high temperature environment, the pores left behind are conducive to the dissipation of water vapor and reduce the possibility of concrete bursting. The other part of the fiber continues to remain in the concrete to improve the crack resistance of the concrete. Therefore, the modified polycrystalline mullite fiber can overlap each other in the concrete to form a network structure, improve the tensile strength of the concrete, reduce brittleness, improve the thermal expansion of the concrete, and improve the fire resistance and high temperature resistance.

[0010] Optionally, the preparation method of the modified polycrystalline mullite fiber is as follows: The alumina nanowire aerogel is added to phenyl silicone resin with a mass of 1 to 1.5 times the mass of the alumina nanowire aerogel, mixed evenly, and then sprayed on the surface of the polycrystalline mullite fiber and dried.

[0011] By adopting the above technical scheme, phenyl silicone resin has good effects in mechanical properties, thermal elasticity, adhesion, etc. because it contains a unique phenyl silicon oxygen chain chemical structure. Therefore, the adhesion of phenyl silicone resin is used to adhere the alumina nanowire aerogel to the surface of the polycrystalline mullite fiber, thereby further improving the tensile resistance of the polycrystalline mullite fiber. In addition, when the concrete temperature is too high, that is, when it reaches 350-450°C, phenyl silicone resin can form a large number of Si-C bonds, combine with O element to form a silicon dioxide layer, block heat, and reduce the thermal expansion of concrete.

[0012] Optionally, the preparation method of the alumina nanowire aerogel is: Alumina nanowire wet gel was synthesized using alumina, glacial acetic acid and deionized water; The wet gel of alumina nanowires was aged, and then placed in a mixture containing silica sol, PAN nanofibers and ethanol. After standing for 22-24 hours, the solvent was replaced with anhydrous ethanol, dried with supercritical carbon dioxide, and heat treated at 300-350° C. for 6-8 hours in a nitrogen atmosphere.

[0013] By adopting the above technical scheme, glacial acetic acid is used to hydrolyze alumina, which has a better and safer catalytic effect, and an alumina nanowire wet gel is obtained. After aging, the solvent is partially evaporated, and the wet gel shrinks slightly, which is convenient for it to be fully contacted with a mixed solution of silica sol, PAN nanofibers and ethanol, and then solvent replacement, supercritical drying and heat treatment are carried out to obtain an alumina nanowire aerogel with a smooth and neat surface, uniform morphology and high strength.

[0014] After heat treatment, part of the solvent and impurities remaining in the alumina nanowire aerogel evaporate as the temperature rises, leaving the pores of the alumina nanowire aerogel, increasing the specific surface area of ​​the alumina nanowire aerogel as a whole, which is beneficial to the diffusion of water vapor in the pores when the concrete is heated, and reducing the probability of concrete expansion and bursting due to heat; and before solvent replacement, the alumina nanowire wet gel is added to a mixture containing silica sol, PAN nanofibers and ethanol, and the silica sol can completely penetrate into the interior of the alumina nanowire wet gel and evenly adhere to the alumina nanowires. After high-temperature heat treatment, the siloxane groups on the surface of the silica sol undergo a dehydration condensation reaction, break bonds under the action of high temperature, and combine with the alumina nanowires, strongly couple with the alumina nanowires at the interface, and form unique chemical bonds, thereby tightly wrapping around the alumina nanowires. This chemical bonding can enhance the interface between the alumina nanowires and bond adjacent alumina nanowires. In addition, the bonding effect of the silica sol can also bond adjacent PAN nanofibers and adjacent PAN The nanofibers and alumina nanowires are bonded to enhance the interfacial bonding strength, so that the three-dimensional network structure of the alumina nanowire aerogel has elasticity and higher mechanical strength under load, strong load resistance and high crack resistance. Therefore, the bonding effect between the alumina nanowires and PAN nanofibers is cross-linked by silica sol to overcome the van der Waals brittleness between the alumina nanowires, so that it has good resistance to environmental damage. The tensile force of the alumina nanowire aerogel is enhanced, and the nanowire network structure inside the alumina nanowire aerogel is interwoven, so that it has outstanding compression strength and can resist external damage to a greater extent. At the same time, the bonding effect of silica sol on the nanowires increases the strength of the nanowire structure's ability to resist strain and crack resistance. In addition, due to the large internal cross-linking density in the alumina nanowire aerogel, it has a strong ability to resist the outside world and has good thermal stability. In addition, the alumina nanowire aerogel plays a heat-insulating role in concrete, which can reduce heat conduction and reduce the heating temperature of the concrete lining segment, and is not easy to expand and burst when heated.

[0015] Under the bonding effect of silica sol, PAN nanofibers are dispersed and adhered to alumina nanowires, and overlap with each other to form a network structure, which further improves the tensile and crack resistance of alumina nanowires. In addition, PAN nanofibers undergo cyclization reaction during high-temperature heat treatment, and the PAN linear structure gradually transforms into a trapezoidal polymerization structure, thus making PAN nanofibers uniquely infusible and heat-resistant. The bonding and coating effect of silica sol can also improve the thermal stability of PAN nanofibers. PAN itself is a polymer, and improving its own thermal stability can avoid the introduction of new combustion sources when it is added to aerogel.

[0016] Optionally, the mass ratio of the alumina nanowire wet gel, silica sol and PAN nanofiber is 10:1-2:1-2.

[0017] By adopting the above technical scheme, the wet gel, silica sol and PAN nanofiber in the above dosage ratio can obtain alumina nanowire aerogel with high strength, tensile strength and thermal stability.

[0018] Optionally, the porous filler is a composite foam material comprising polypropylene and fly ash in a mass ratio of 1:0.05-0.1.

[0019] By adopting the above technical scheme, polypropylene and fly ash are used as raw materials of the composite foam material, and fly ash is used as the skeleton of the polypropylene molecular chain, so that the elasticity and rigidity of the composite foam material are increased, and the fly ash can act as a nucleating agent to increase the foaming effect of polypropylene. The composite foam material has good melt elasticity and increased notch impact strength. When dispersed in concrete, it can improve the crack resistance of concrete. When heated, it can alleviate the thermal expansion of concrete, reduce the generation of high-temperature cracks, and improve the durability of concrete.

[0020] Optionally, the preparation method of the composite foam material is as follows: The polypropylene and silane-modified fly ash are mixed and melt-spun to obtain blended fibers; The blended fiber and the TPV elastomer are mixed, then hot-pressed at 145-160° C. for 10-15 minutes, and then foamed with supercritical carbon dioxide to obtain a composite foam material, wherein the mass ratio of the TPV elastomer to the polypropylene is 0.1-0.15:1.

[0021] By adopting the above technical scheme, the compatibility between silane-modified fly ash and polypropylene is improved, and it can be tightly combined with polypropylene. After co-blending and spinning, blended fibers are obtained, and then the blended fibers are mixed with TPV elastomers and hot-pressed and supercritically foamed, so that the composite material has excellent resilience and wear resistance. The addition of TPV elastomers further improves the uniformity of the bubbles during foaming, reduces the thermal conduction of the composite foaming material, prevents the conduction of heat inside the concrete, reduces the brittleness of the concrete when subjected to high temperatures, makes the temperature gradient inside the material smoother, reduces stress concentration and cracking risks under high temperatures, and the microporous structure produced by supercritical foaming can also increase the surface area and relative flexibility of the material, improve the impact resistance of the concrete, achieve the toughening effect, and effectively prevent the expansion of cracks and improve fracture toughness.

[0022] Optionally, the supercritical carbon dioxide foaming temperature is 155-165° C., the pressure is 20-28 MPa, and the foaming time is 10-20 min.

[0023] By adopting the above technical solution and the above supercritical foaming parameters, the micropores in the composite foaming material can be made more continuous and uniform.

[0024] Optionally, the gravel includes gravel A and gravel B with a mass ratio of 2.3:9.05-9.7, gravel A is graded crushed stone with a particle size of 5-10 mm, and gravel B has a particle size of 10-20 mm.

[0025] By adopting the above technical solution, two kinds of gravel with different particle sizes are used with reasonable grading, and are filled with fly ash, cement, etc., so as to improve the compressive strength of concrete.

[0026] Optionally, the fly ash is Class F Grade I fly ash, and the admixture is an air-entraining water-reducing agent.

[0027] By adopting the above technical solution, the fineness of Class I fly ash is small, and it can be filled between the raw material particles, thereby improving the density of concrete, reducing the bleeding and segregation of concrete, and improving fluidity and filling properties.

[0028] Air-entraining water reducer can significantly reduce the surface tension of mixing water, improve the workability of concrete, reduce the bleeding and segregation of concrete by introducing tiny bubbles, improve the uniformity and stability of concrete, improve its impermeability and frost resistance, enhance its durability and extend its service life.

[0029] In a second aspect, the present application provides a method for preparing concrete for prefabricated lining segments, which adopts the following technical solution: A method for preparing concrete for prefabricated lining segments comprises the following steps: Add the admixture to water 20 times its mass, and introduce compressed air to obtain foam liquid; Mixing cement, sand, gravel, fly ash, modified polycrystalline mullite fiber, porous filler and balance water to prepare a blend; The foam liquid is added into the mixed material, and stirred evenly to obtain concrete for prefabricated lining segments.

[0030] By adopting the above technical scheme, the admixture is dissolved in water, foamed by compressed air, and the foam liquid is added to the blend. The foam liquid can be fully mixed with the raw materials, and its ball effect is used to improve the workability and fluidity of the concrete slurry.

[0031] In summary, this application has the following beneficial effects: 1. Since the present application adopts modified polycrystalline mullite fiber and porous filler in concrete raw materials, and the modified polycrystalline mullite fiber is made of mullite fiber loaded with alumina nanowire aerogel, the polycrystalline mullite fiber has high temperature resistance and mechanical properties, and low thermal conductivity, and has a good effect of alleviating the heating condition of concrete, reducing thermal cracking, and enhancing the compressive strength of concrete. The alumina nanowire aerogel has a high specific surface area, high thermal stability, and low thermal conductivity, which can improve the compressive strength of concrete, improve its heat resistance, and reduce the possibility of thermal cracking.

[0032] 2. In the present application, it is preferred to add silica sol and PAN nanofibers when preparing alumina nanowire aerogel, which can improve the interface effect between alumina nanowires, enhance mechanical strength and load resistance, increase its thermal insulation effect, reduce heat conduction, and enhance the fire resistance of concrete.

[0033] 3. In the present application, polypropylene, fly ash and TPV elastomer are preferably used to prepare the composite foam material. Fly ash can increase the crystallinity of polypropylene and improve its impact strength, while TPV elastomer can improve the mechanical strength of the blended fiber, thereby improving the flexural properties of concrete. In addition, it can also improve the uniformity of the pores of the composite foam material and improve the high temperature resistance and crack resistance of the concrete. DETAILED DESCRIPTION

[0034] The following examples further illustrate the present application in detail.

[0035] Preparation Example 1-8 of Modified Polycrystalline Mullite Fiber Preparation Example 1: (1) Add 37.3 g of aluminum oxide nanopowder to 400 ml of deionized water, stir and dissolve for 30 min, add 20 g of diluted glacial acetic acid, seal and heat to 230° C., react for 5.5 h, cool and obtain aluminum oxide nanowire wet gel; (2) aging the wet alumina nanowire gel at 90° C. for 2.5 h, then immersing it in anhydrous ethanol for solvent replacement, the replacement time is 3 days, and the replacement is performed 3 times, and then supercritical carbon dioxide drying is performed at a drying temperature of 35° C. and a pressure of 7.5 MPa to obtain an alumina nanowire aerogel; (3) 40 g of alumina nanowire aerogel was dispersed in 60 g of deionized water, 100 g of polycrystalline mullite fiber was added, the mixture was stirred evenly, and dried at 70 °C to obtain modified polycrystalline mullite fiber. The polycrystalline mullite fiber was selected from Zibo Santaishan Energy Saving Materials Co., Ltd., with a product number of SS-PMF1700, a fiber diameter of 3 μm, and a length of 12 mm.

[0036] Preparation Example 2: (1) 37.3 g of aluminum oxide nanopowder was added to 400 ml of deionized water, stirred and dissolved for 30 min, 20 g of diluted glacial acetic acid was added, the mixture was sealed and heated to 230° C., reacted for 5.5 h, and cooled to obtain aluminum oxide nanowire wet gel; (2) aging the wet alumina nanowire gel at 90° C. for 2.5 h, then immersing it in anhydrous ethanol for solvent replacement, the replacement time is 3 days, and the replacement is performed 3 times, and then supercritical carbon dioxide drying is performed at a drying temperature of 35° C. and a pressure of 7.5 MPa to obtain an alumina nanowire aerogel; (3) 20 g of alumina nanowire aerogel was dispersed in 20 g of deionized water, 100 g of polycrystalline mullite fiber was added, the mixture was stirred evenly, and dried at 70 °C to obtain modified polycrystalline mullite fiber. The polycrystalline mullite fiber was selected from Zibo Santaishan Energy Saving Materials Co., Ltd., with a product number of SS-PMF1700, a fiber diameter of 3 μm, and a length of 12 mm.

[0037] Preparation Example 3: (1) Add 37.3 g of aluminum oxide nanopowder to 400 ml of deionized water, stir and dissolve for 30 min, add 20 g of diluted glacial acetic acid, seal and heat to 230° C., react for 5.5 h, cool and obtain aluminum oxide nanowire wet gel; (2) aging the wet alumina nanowire gel at 90° C. for 2.5 h, then immersing it in anhydrous ethanol for solvent replacement, the replacement time is 3 days, and the replacement is performed 3 times, and then supercritical carbon dioxide drying is performed at a drying temperature of 35° C. and a pressure of 7.5 MPa to obtain an alumina nanowire aerogel; (3) 20 g of alumina nanowire aerogel was added to 20 g of phenyl silicone resin, mixed evenly, and then sprayed on the surface of 100 g of polycrystalline mullite fiber, and dried at 70 ° C to obtain modified polycrystalline mullite fiber. The phenyl silicone resin was selected from Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd., model JP-MKV9604, and the polycrystalline mullite cellulose was selected from Zibo Santaishan Energy Saving Materials Co., Ltd., product number SS-PMF1700. The fiber diameter was 3 μm and the length was 12 mm.

[0038] Preparation Example 4: (1) 37.3 g of aluminum oxide nanopowder was added to 400 ml of deionized water, stirred and dissolved for 30 min, 20 g of diluted glacial acetic acid was added, the mixture was sealed and heated to 230° C., reacted for 5.5 h, and cooled to obtain aluminum oxide nanowire wet gel; (2) aging the wet alumina nanowire gel at 90° C. for 2.5 h, then immersing it in anhydrous ethanol for solvent replacement, the replacement time is 3 days, and the replacement is performed 3 times, and then supercritical carbon dioxide drying is performed at a drying temperature of 35° C. and a pressure of 7.5 MPa to obtain an alumina nanowire aerogel; (3) 40 g of alumina nanowire aerogel was added to 60 g of phenyl silicone resin, mixed evenly, and then sprayed on the surface of 100 g of polycrystalline mullite fiber, and dried at 70 ° C to obtain modified polycrystalline mullite fiber. The phenyl silicone resin was selected from Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd., model JP-MKV9604, and the polycrystalline mullite cellulose was selected from Zibo Santaishan Energy Saving Materials Co., Ltd., product number SS-PMF1700. The fiber diameter was 3 μm and the length was 12 mm.

[0039] Preparation Example 5: (1) Add 37.3 g of aluminum oxide nanopowder to 400 ml of deionized water, stir and dissolve for 30 min, add 20 g of diluted glacial acetic acid, seal and heat to 230° C., react for 5.5 h, cool and obtain aluminum oxide nanowire wet gel; (2) 40 g of alumina nanowire wet gel was aged at 90° C. for 2.5 h, then placed in a mixed solution containing 8 g of silica sol, 8 g of PAN nanofibers and 160 g of ethanol, and allowed to stand for 24 h before being immersed in anhydrous ethanol for solvent replacement. The replacement time was 3 days, and the replacement was performed 3 times. Then, supercritical carbon dioxide drying was performed at a drying temperature of 35° C. and a pressure of 7.5 MPa. In a nitrogen atmosphere, heat treatment was performed at 350° C. for 6 h to obtain alumina nanowire aerogel. PAN nanofibers were selected from Shandong Luxian Building Materials Technology Co., Ltd. and had a length of 3 mm. Silica sol was selected from Henan Jinrun New Materials Co., Ltd. and had a product number of JR1007b and a content of 30%. (3) 40 g of alumina nanowire aerogel was added to 60 g of phenyl silicone resin, mixed evenly, and then sprayed on the surface of 100 g of polycrystalline mullite fiber, and dried at 70 ° C to obtain modified polycrystalline mullite fiber. The phenyl silicone resin was selected from Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd., model JP-MKV9604, and the polycrystalline mullite cellulose was selected from Zibo Santaishan Energy Saving Materials Co., Ltd., product number SS-PMF1700. The fiber diameter was 3 μm and the length was 12 mm.

[0040] Preparation Example 6: The difference from Preparation Example 5 is that in step (2), the amount of silica sol in the mixed solution is 4 g, the amount of PAN nanofiber is 4 g, the heat treatment temperature is 300°C, and the time is 8 h.

[0041] Preparation Example 7: The difference from Preparation Example 5 is that PAN nanofibers are not added.

[0042] Preparation Example 8: The difference from Preparation Example 5 is that no silica sol is added.

[0043] Preparation Examples 9-13 of Composite Foam Materials In the following preparation examples, polypropylene is selected from Maoming Petrochemical, model PPH-T03, fly ash is ultrafine fly ash, selected from Lingshou County Zhan Teng Mineral Products, product number 96-BG, TPV elastomer is Shenzhen Hengsheng Plastic Chemical, model 121-75M200.

[0044] Preparation Example 9: (1) 100 g of polypropylene and fly ash were mixed in a mass ratio of 1:0.05, extruded and granulated to obtain a composite material, the temperatures of zones 1-8 of the extruder were 170° C., 175° C., 175° C., 175° C., 180° C., 180° C., 175° C., 180° C., 175° C., respectively, the die temperature was 170° C., the screw speed was 450 r / min, the fly ash was modified by immersing in an ethanol solution of silane coupling agent KH550 at room temperature for 3 h, and the mass ratio of fly ash to silane coupling agent KH550 was 1:0.01; (2) The composite material was dried at 80°C for 4 h, then mixed with sodium bicarbonate in a mass ratio of 100:2.5, injection molded at 200°C and a pressure of 50 MPa, and then crushed to form granules with a particle size of 5 mm. The injection speed was 90%, the injection time was 0.6 s, and the cooling time was 20 s.

[0045] Preparation Example 10: (1) 100 g of polypropylene and fly ash were mixed uniformly in a mass ratio of 1:0.05, melt-spun, stretched at a speed of 10 mm / min at 140° C. to an elongation of 150%, shaped at 140° C., and cooled to obtain a blended fiber. The spinning temperature was 220° C. The fly ash was modified in advance by immersing in an ethanol solution of a silane coupling agent KH550 at room temperature for 3 h. The mass ratio of fly ash to silane coupling agent KH550 was 1:0.01. (2) The blended fiber and TPV elastomer are mixed, hot-pressed at 160°C for 15 minutes, and then foamed with supercritical carbon dioxide at a foaming temperature of 165°C, a pressure of 28 MPa, and a time of 10 minutes. The mass ratio of TPV elastomer to polypropylene is 0.1:1.

[0046] Preparation Example 11: (1) 100 g of polypropylene and fly ash were mixed uniformly in a mass ratio of 1:0.1, melt-spun, stretched at a speed of 10 mm / min at 140° C. to an elongation of 150%, shaped at 140° C., and cooled to obtain a blended fiber. The spinning temperature was 220° C. The fly ash was preliminarily modified by immersing in an ethanol solution of a silane coupling agent KH550 at room temperature for 3 h. The mass ratio of fly ash to silane coupling agent KH550 was 1:0.01. (2) The blended fiber and TPV elastomer are mixed, hot-pressed at 145°C for 10 min, and then foamed with supercritical carbon dioxide at a foaming temperature of 155°C, a pressure of 20 MPa, and a time of 30 min. The mass ratio of TPV elastomer to polypropylene is 0.15:1.

[0047] Preparation Example 12: The difference from Preparation Example 11 is that no TPV elastomer is used, and the blended fiber is a composite foaming material.

[0048] Preparation Example 13: The difference from Preparation Example 11 is that polypropylene, fly ash and TPV elastomer in a mass ratio of 1:0.1:0.15 are evenly mixed, and during melt extrusion and granulation, the temperatures of extruder zones 1-8 are 175°C, 180°C, 180°C, 180°C, 185°C, 185°C, 185°C, and 180°C, respectively. Supercritical foaming is performed with a foaming temperature of 155°C, a pressure of 20 MPa, and a time of 30 min to obtain a composite foaming material. The fly ash is pre-modified by immersing it in an ethanol solution of silane coupling agent KH550 for 3 hours at room temperature, and the mass ratio of fly ash to silane coupling agent KH550 is 1:0.01. Example

[0049] The sources of raw materials in each example are shown in Table 1.

[0050] Table 1 Sources of raw materials in Example 1 Example 1: A concrete for prefabricated lining segments, the raw material dosage is as shown in Table 2, wherein the gravel includes gravel A and gravel B with a mass ratio of 2.3:9.05, the admixture is an air-entraining water reducer, the modified polycrystalline mullite fiber is prepared by Preparation Example 1, and the porous filler is expanded clay with a particle size of 5 mm.

[0051] The method for preparing the above-mentioned concrete for prefabricated lining segments comprises the following steps: S1. Add the admixture to water 20 times its mass, introduce compressed air at a pressure of 0.05 MPa for 15 min to obtain a foam solution; S2, mixing cement, sand, gravel, fly ash, modified polycrystalline mullite fiber, porous filler and balance water to prepare a blend; S3. Add the foam liquid into the mixed material, stir evenly, and obtain concrete for prefabricated lining segments.

[0052] Table 2 Raw material consumption of concrete for prefabricated lining segments in Examples 1-3 Example 2: A concrete for prefabricated lining segments, which differs from Example 1 in that the amounts of raw materials are as shown in Table 2, and the modified polycrystalline mullite fiber is prepared by Preparation Example 2.

[0053] Example 3: A concrete for prefabricated lining segments, which differs from Example 1 in that the amounts of raw materials are as shown in Table 2.

[0054] Example 4: A concrete for prefabricated lining segments, which differs from Example 1 in that the modified polycrystalline mullite fiber is made from Preparation Example 3.

[0055] Example 5: A concrete for prefabricated lining segments, which differs from Example 1 in that the modified polycrystalline mullite fiber is made from Preparation Example 4.

[0056] Example 6: A concrete for prefabricated lining segments, which differs from Example 5 in that the modified polycrystalline mullite fiber is made from Preparation Example 5.

[0057] Example 7: A concrete for prefabricated lining segments, which differs from Example 5 in that the modified polycrystalline mullite fiber is made from Preparation Example 6.

[0058] Example 8: A concrete for prefabricated lining segments, which differs from Example 6 in that the modified polycrystalline mullite fiber is made from Preparation Example 7.

[0059] Example 9: A concrete for prefabricated lining segments, which differs from Example 6 in that the modified polycrystalline mullite fiber is made from Preparation Example 8.

[0060] Example 10: A concrete for prefabricated lining segments, which differs from Example 1 in that the porous filler is a composite foam material comprising polypropylene and fly ash, and is made from Preparation Example 9.

[0061] Example 11: A concrete for prefabricated lining segments, which differs from Example 1 in that the porous filler is a composite foam material comprising polypropylene and fly ash, and is made from Preparation Example 10.

[0062] Example 12: A concrete for prefabricated lining segments, which differs from Example 1 in that the porous filler is a composite foam material comprising polypropylene and fly ash, and is made from Preparation Example 11.

[0063] Example 13: A concrete for prefabricated lining segments, which differs from Example 12 in that the porous filler is a composite foam material comprising polypropylene and fly ash, and is made from Preparation Example 12.

[0064] Example 14: A concrete for prefabricated lining segments, which differs from Example 12 in that the porous filler is a composite foam material comprising polypropylene and fly ash, and is made from Preparation Example 13.

[0065] Example 15: A concrete for prefabricated lining segments, which differs from Example 1 in that the modified polycrystalline mullite fiber is made from Preparation Example 5, and the porous filler is a composite foam material comprising polypropylene and fly ash, which is made from Preparation Example 11.

[0066] Comparative Example Comparative Example 1: A concrete for prefabricated lining segments, which differs from Example 1 in that an equal amount of porous filler is used to replace the modified polycrystalline mullite fiber.

[0067] Comparative Example 2: A concrete for prefabricated lining segments, which differs from Example 1 in that no porous filler is added.

[0068] Comparative Example 3: A concrete for prefabricated lining segments, which differs from Example 1 in that modified polycrystalline mullite fibers and porous fillers are not added.

[0069] Performance testing Concrete was prepared according to the methods in the examples and comparative examples, and performance tests were performed with reference to the following methods. The test results are recorded in Table 3.

[0070] 1. Compressive strength: Tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0071] 2. Tensile strength: Tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0072] 3. High temperature characteristics: pour the prepared concrete into a mold to make a cubic specimen with a size of 100mm×100mm×100mm. Demould it after curing at 22℃ and 95% humidity for 28 days and dry it to constant weight at 105℃. During the test, place the test specimens in a box-type resistance furnace in groups of 3. Heat the temperature to 200℃, 400℃, 600℃ and 800℃ at a rate of 5℃ / min. Start timing for 30 minutes when the temperature reaches the preset temperature. After the combustion is completed, open the furnace door and cool the specimen to room temperature. Test the compressive strength residual rate: α=Ft / Fo×100%, Ft is the compressive strength measured at high temperature, and Fo is the compressive strength measured at room temperature.

[0073] Table 3 Performance test of concrete for prefabricated lining segments Combining Examples 1-3 and the data in Table 3, it can be seen that the modified polycrystalline mullite fibers prepared in Preparation Examples 1 and 2 in Examples 1-3, i.e., the alumina nanowire aerogel is loaded on the polycrystalline mullite fibers, can be seen that the prepared concrete has high 26d compressive strength and 28d flexural strength. After different high-temperature treatments, the compressive strength residual rate is higher than 73% at 200°C, and has strong resistance to high-temperature expansion and high-temperature bursting.

[0074] Compared with Example 1, Examples 4 and 5 use the modified polycrystalline mullite fibers prepared in Preparation Examples 3 and 4, respectively, wherein phenyl silicone resin is used instead of deionized water. From the comparison of the data in Table 3, it can be seen that the mechanical strength of the concrete prepared in Examples 4 and 5 is better than that in Example 1, and the high temperature resistance is improved.

[0075] In Example 6 and Example 7, the modified polycrystalline mullite fibers prepared in Preparation Example 5 and Preparation Example 6 are used respectively. Compared with Example 5, the compressive strength and flexural strength of the concrete prepared in Examples 6-7 are increased, and after being treated at different high temperatures for 30 minutes, the residual rate of the compressive strength is increased, and the high temperature crack resistance is enhanced.

[0076] In Example 8 and Example 9, the modified polycrystalline mullite fibers prepared in Preparation Example 7 and Preparation Example 8 are used respectively. Compared with Example 6, the compressive strength and flexural strength of the concrete prepared in Example 8 and Example 9 are slightly reduced, and the high temperature resistance is weakened.

[0077] In Example 10, the composite foam material prepared in Preparation Example 9 is used to blend, melt and granulate polypropylene and fly ash. Compared with Example 1, the flexural strength of the concrete is increased, and after high temperature, the residual compressive strength is improved.

[0078] In Example 11 and Example 12, the composite foam materials prepared in Preparation Example 10 and Preparation Example 11 are used respectively, polypropylene and fly ash are mixed and then hot-melt spun, and then modified with TPV elastomer. Compared with Example 1, it can be seen from the data in Table 3 that the flexural strength of the concrete prepared in Examples 11-12 is significantly increased, and after high-temperature treatment, the residual rate of compressive strength is better than that of Example 10.

[0079] In Example 13, the composite foam material prepared in Preparation Example 12 was used. Compared with Preparation Example 11 in Example 12, no TPV elastomer was added. As can be seen from Table 3, the flexural strength of the concrete decreased and the heat resistance effect was slightly weakened.

[0080] In Example 14, the composite foam material prepared in Preparation Example 13 is used to blend polypropylene, fly ash and TPV elastomer into granules. It can be seen that the flexural strength of the concrete is weak and the heat resistance is slightly reduced.

[0081] In Example 15, the optimal modified polycrystalline mullite fiber and the optimal composite foaming material are used. It can be seen that the concrete obtained thereby has better mechanical strength and heat resistance, and can reduce the bursting phenomenon under high temperature.

[0082] Compared with Example 1, in Comparative Example 1, an equal amount of porous filler is used to replace the modified polycrystalline mullite fiber. It can be seen that the compressive strength of the concrete is increased, but the flexural strength is significantly reduced. Moreover, due to the high porosity, the temperature difference between the inside and outside of the concrete is large when heated, which easily leads to a decrease in the bearing capacity.

[0083] In Comparative Example 2, no porous filler was added. Compared with Example 1, the compressive strength of the concrete prepared in Comparative Example 2 decreased, the mechanical strength of the concrete decreased, and the heat resistance decreased.

[0084] In Comparative Example 3, no modified polycrystalline mullite fiber and porous filler were added. Compared with Example 1, the mechanical strength and heat resistance of the concrete were both reduced.

[0085] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A concrete for prefabricated lining segments, characterized in that: The invention comprises the following raw materials in parts by weight: 380-400 parts of cement, 720-750 parts of sand, 1135-1200 parts of stone, 130-150 parts of water, 50-60 parts of fly ash, 5.16-5.5 parts of admixture, 90-100 parts of modified polycrystalline mullite fiber, and 45-50 parts of porous filler; The modified polycrystalline mullite fiber comprises polycrystalline mullite fiber and alumina nanowire aerogel loaded on the surface thereof, and the mass ratio of the polycrystalline mullite fiber to the alumina nanowire aerogel is 1:0.2-0.

4.

2. The concrete for prefabricated lining segments according to claim 1, characterized in that: The preparation method of the modified polycrystalline mullite fiber is as follows: The alumina nanowire aerogel is added to phenyl silicone resin with a mass of 1 to 1.5 times the mass of the alumina nanowire aerogel, mixed evenly, and then sprayed on the surface of the polycrystalline mullite fiber and dried.

3. The concrete for prefabricated lining segments according to claim 2, characterized in that: The preparation method of the alumina nanowire aerogel: Alumina nanowire wet gel was synthesized using alumina, glacial acetic acid and deionized water; The wet gel of alumina nanowires was aged, and then placed in a mixture containing silica sol, PAN nanofibers and ethanol. After standing for 22-24 hours, the solvent was replaced with anhydrous ethanol, dried with supercritical carbon dioxide, and heat treated at 300-350° C. for 6-8 hours in a nitrogen atmosphere.

4. The concrete for prefabricated lining segments according to claim 3 is characterized in that: The mass ratio of the aluminum oxide nanowire wet gel, the silica sol and the PAN nanofiber is 10:1-2:1-2.

5. The concrete for prefabricated lining segments according to claim 1, characterized in that: The porous filler is a composite foam material containing polypropylene and fly ash in a mass ratio of 1:0.05-0.

1.

6. The concrete for prefabricated lining segments according to claim 5, characterized in that: The preparation method of the composite foam material is as follows: The polypropylene and silane-modified fly ash are mixed and melt-spun to obtain blended fibers; The blended fiber and the TPV elastomer are mixed, then hot-pressed at 145-160° C. for 10-15 minutes, and then foamed with supercritical carbon dioxide to obtain a composite foam material, wherein the mass ratio of the TPV elastomer to the polypropylene is 0.1-0.15:

1.

7. The concrete for prefabricated lining segments according to claim 6, characterized in that: The supercritical carbon dioxide foaming temperature is 155-165° C., the pressure is 20-28 MPa, and the foaming time is 10-20 min.

8. The concrete for prefabricated lining segments according to claim 1, characterized in that: The stones include stone A and stone B with a mass ratio of 2.3:9.05-9.7, stone A is graded crushed stone with a particle size of 5-10 mm, and stone B has a particle size of 10-20 mm.

9. The concrete for prefabricated lining segments according to claim 1, characterized in that: The fly ash is Class F Grade I fly ash, and the admixture is an air-entraining water-reducing agent.

10. The method for preparing concrete for prefabricated lining segments according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add the admixture to water 20 times its mass, and introduce compressed air to obtain foam liquid; Mixing cement, sand, gravel, fly ash, modified polycrystalline mullite fiber, porous filler and balance water to prepare a blend; The foam liquid is added into the mixed material, and stirred evenly to obtain concrete for prefabricated lining segments.